Multiple antibacterial resistance in isolates from Thoroughbred horses in the racecourse «La Rinconada», Caracas, Venezuela - Morales B., Abelardo (2010)
Multiple resistance to antibiotics was determined in bacterial isolates from Thoroughbred horses at the National Race Track «La Rinconada», Caracas, Venezuela. From a population of 128 horses in 2009, 12 did not respond to antibacterial treatment despite being treated for 7 days with gentamicin (6 mg/kg), penicillin (22,000 IU/kg) and ceftiofur (4 mg/kg). Necropsy was conducted and tissue samples were collected from abscesses in septic arthritis (4), abscess in endocardium (1), suppurative esophagitis (2), laryngeal granuloma (1), pneumonia (2), pyelonephritis (1) and dermatitis (1). Samples were placed in Stuart transport medium and cultured. The bacterial isolates were tested for antibiotic susceptibility. E. coli was isolated in 12 cases (75%), Proteus mirabilis in 2 (12.5%), Pseudomonas aeruginosa in 1 (6.25%), and Streptococcus equi subspecies zooepidemicus in 1 (6.25%). The bacterial isolates showed resistance to gentamicin, ciprofloxacin, nalidixic acid, trimethoprim, ampicillin and amikacin.